TRANSFORMATIONAL LEADERSHIP AND ORGANISATIONAL COMMITMENT: KEY DRIVERS OF LECTURER PERFORMANCE IN MUHAMMADIYAH HIGHER EDUCATION INSTITUTIONS IN INDONESIA - Hadi, Muhammad Fikry; Yasin, Nurul Hafizah Mohd (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2026)
Lecturers often face challenges such as excessive administrative workloads, limited research support, and increasing performance expectations that can impede their effectiveness. Hence, this study aims to examine how transformational leadership and organisational commitment influence lecturers’ performance, providing insights into strategies for improving academic productivity and institutional outcomes. Employing a quantitative approach with a cross-sectional survey design, data were collected using a validated and reliable questionnaire. Stratified sampling based on institutional accreditation produced 292 usable responses from 300 distributed questionnaires. The data were analysed using multiple linear regression techniques. The results demonstrate that transformational leadership has a positive and significant effect on lecturer performance, while organisational commitment similarly contributes positively and significantly influences lecturer performance. These findings confirm that the combination of transformational leadership and organisational commitment serves as a pivotal driver of faculty academic achievement. Practically, the study highlights the necessity of fostering transformational leadership capacity across managerial levels and reinforcing organisational commitment through performance-orientated policies and research support, thereby strengthening the long-term competitiveness of Muhammadiyah higher education institutions at both national and global scales.